Exploring the integration of school food gardens as a learning and food security tool at a primary school in Orlando West, Soweto - Buthelezi, Bridget Snethemba Samukelisiwe (University of the Witwatersrand, Johannesburg, 2024)
In a school environment, the school food garden serves a variety of purposes. However, in the South African context, there are limited studies that have explored the multifaceted nature of school food gardens. Against this backdrop, the study aims to investigate how a primary school in Soweto works with a food garden to support learning and ensure food security. The data for this qualitative research study was collected through semi-structured interviews with a purposive sampling of four participants, including the principal and three teachers. The transcribed data was coded into themes that were identified and analysed (guided by the GREEN tool which was created by Burt et al. (2016)). The findings show that the purpose of the school food garden is to enhance teaching and learning, as well as to supplement the school's feeding program. Further, the study found that, apart from challenges such as resource shortages and time limitations, learners perceive partaking in school gardening activities as punishment. The study advocates for the need for collaboration with different stakeholders, particularly the government and communities, to span the resource gap and time constraints. Furthermore, it recommends teacher training for the successful integration of the food garden as a teaching and learning tool into the curriculum to reduce negative learners’ perceptions of their use in curriculum content delivery.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; School food garden; Experiential learning; Feeding Scheme; SDG-4: Quality education